The Effect of Marketing Communication Strategy, Brand Attitude, and Brand Loyalty on Repurchase Intention of Halal Cosmetics - Eqy Farha Gunawan; Siti Nurlaela (International Journal of Economics (IJEC), 2025)
This study aims to analyze the influence of marketing communication strategy, which includes traditional media communication, firm-created social media communication, user-generated social media communication, and personal selling communication on brand attitude, and to analyze the role of brand attitude as an intermediary in the relationship between marketing communication strategy and brand loyalty and repurchase intention among halal cosmetic consumers in Indonesia. A quantitative approach was used with a survey method of 138 respondents who used halal cosmetics. Data testing was carried out using Structural Equation Modeling (SEM) with SmartPLS 4. The results showed that all marketing communication variables had a positive effect on brand attitude. Furthermore, brand attitude was proven to be an intermediary in the relationship between marketing communication strategy and brand loyalty and repurchase intention. These findings provide implications for halal cosmetic companies in optimizing marketing communication strategies that pay attention to the formation of positive brand attitudes to increase customer loyalty and repurchase intention.